Sustainable geopolymer adsorbents utilizing silica fume as a partial replacement for metakaolin in the removal of copper ion from synthesized copper solution - Pilomeena Arokiasamy; Mohd Mustafa Al Bakri Abdullah; Eva Arifi; Noorina Hidayu Jamil; Md Azree Othuman Mydin; Shayfull Zamree Abd Rahim; Andrei Victor Sandu; Shafiq Ishak (Case Studies in Construction Materials)
Biochar has great significance for controlling heavy metal pollution. Nevertheless, its application is impeded by certain shortcomings, such as a limited adsorption capacity, a slow adsorption rate, and poor reusability. Besides, the physical adsorption capacity of raw biochar to heavy metals is suboptimal. As a result, researchers prefer to use geopolymer-based adsorbents for the removal of heavy metals due to their excellent immobilization effect. However, no research has been done on the synthesis of geopolymer-based adsorbent using silica fume for heavy metal adsorption. Thus, the aim of this study is to partially replace metakaolin (MK) with silica fume (S1) (25, 50, 75 and 100 %) in geopolymer formulation at varied S:L ratio (0.4, 0.6, 0.8 and 1.0) to study the impact on the geopolymerization and its following properties in the removal efficiency of copper (Cu2 +). Characterization techniques such as Energy dispersive X-ray fluorescence (EDXRF), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), Scanning electron microscope (SEM) and Energy dispersive X-ray spectroscopy (EDX) were used to study the physicochemical properties of the developed geopolymer. The concentration of Cu2+ before and after adsorption was determined by Atomic absorption spectroscopy (AAS) and the removal efficiency was calculated. Based on the experimental result, the geopolymer prepared with 25 % MK and 75 % S1 at S:L of 0.6 maintained the high removal efficiency of Cu2+ (99.62 %) with 100 % MK geopolymer (98.56 %). The generation of N-A-S-H gel with the 75 % replacement level of S1 producing more reactive Si and Al binding sites for Cu2+ adsorption. In addition, S1 contains exchangeable cations such as Ca2+, Mg2+ and Na+ which further promote the adsorption of Cu2+ by ion exchange. Moreover, the mechanisms such as chemical bonding and precipitation were involved in the adsorption of Cu2+. Hence, this research could serve as a basis for the development of solid waste based geopolymers that could remove heavy metal ions from aqueous solution.